The radiographer's perspective on X-ray examinations in potentially pregnant patients; results of a focus group study among Dutch radiographers. Issue 2 (May 2022) - Wit, F.; Vroonland, C.C.J.J.; Bijwaard, H.
Abstract: Introduction: The Netherlands does not have a national guideline for performing radiographic examinations on pregnant patients. Radiographic examination is a generic term for all examinations performed using ionizing radiation, including but not limited to radiographs, fluoroscopy and computed tomography. A pilot study amongst radiographers (Medical Radiation Technologists (MRTs)) showed that standardized practice of radiographic examinations on pregnant women is not evident between Radiology departments and that there is a need for a national guideline as the varying practice methods may lead to confusion and uncertainty amongst both patients and MRTs. Methods: Focus groups consisting of MRTs from several Radiology departments within the Netherlands were used to map ideas and requirements as to what should be included in the national guideline. Nine focus group sessions were organized with a total of 52 participants. Using a previous review (Wit, Fleur; Vroonland, Colinda; Bijwaard H. Pre-natal X-ray exposure and the risk of developing paediatric cancer; a systematic review of risk factors and a comparison of international guidelines. Health Physics 2021; 121 (3):225–233), the following key points were chosen as discussion topics for the focus group sessions: dose reduction, confirming pregnancy and risk communication. Results: Results showed that the participating MRTs did not agree on the use of lead aprons. That the national guideline should include standardized methods to adjust parameters to decrease radiation dose. Focus group participants find it difficult to ask a patient's pregnancy status, especially when dealing with relatively young and old (er) patients. When communicating the level of risk associated with a radiographic examination the participating MRTs would like to be able to use examples and comparisons, preferably by means of a multilingual website. Conclusion: A national guideline must include information on justification, available alternatives, dose reductions methods and confirmation of pregnancy requirements when fetal dose is a significant risk. Implications for practice: A national guideline ensures standardized practice can be implemented in Radiology departments, increasing clarity of the issues for both patients and MRTs.